Fantasizing the Body in Sones’ What My Mother Doesn’t Know - Thapa, Hukum (JODEM: Journal of Language and Literature, 2023)
The present paper explores fantasizing the body in Sones’ What My Mother Doesn’t Know. It contends that fantasy stands as an emerging activity in the lives of the teenagers or adolescents or young adults during the grown up stage. They are in particular enthusiastic to fantasize their bodies. The young adult protagonist Sophie Stein in What My Mother Doesn’t Know fantasizes her and others’ body in many conditions. So, it attempts to unearth how and why Sophie Stein fantasizes own and others’ body. It argues that fantasizing about the body functions as an agency to explore the events of happiness and to reduce the distress, frustration and anxiety. It further claims that fantasizing about the body supports the young adults to acquire their freedom, identity and maturity. For this purpose, it employs the critical insights of R. Craig Roney, Jerome L. Singer, Loyola McLean et al., Karen Coats and Pamela S. Gates et al. This study expects to open an avenue for further research about fantasy and young adults comprising the milieu of different continents and societies.